Integrated population model reveals human- and environment-driven changes in Baltic ringed seal Pusa hispida botnica demography and behavior - Ersalman, Murat; Kunnasranta, Mervi; Ahola, Markus; Carlsson, Anja M.; Persson, Sara; Bäcklin, Britt-Marie; Helle, Inari; Cervin, Linnea; Vanhatalo, Jarno (Inter-Research Science Center, 2025)
Integrated population models (IPMs) are a promising approach to test ecological theories and assess wildlife populations in dynamic and uncertain conditions. By combining multiple data sources into a unified model, they enable the parametrization of versatile, mechanistic models that can predict population dynamics in novel circumstances. Here, we present a Bayesian IPM for the ringed seal Pusa hispida botnica population inhabiting the Bothnian Bay in the Baltic Sea. Despite the availability of long-term monitoring data, traditional assessment methods have faltered due to dynamic environmental conditions, varying reproductive rates, and recently re-introduced hunting, thus limiting the quality of information available to managers. We fit our model to census and various demographic, reproductive, and harvest data from 1988 to 2023 to provide a comprehensive assessment of past population trends, and predict population response to alternative hunting scenarios. We estimated that 20000-36000 ringed seals inhabited the Bothnian Bay in 2024, increasing at a rate of 3-6% yr-1. Reproductive rates have increased since 1988, leading to a substantial increase in the growth rate up until 2015. However, the re-introduction of hunting has since reduced the growth rate, and even minor quota increases are likely to reduce it further. Our results also support the hypothesis that a greater proportion of the population hauls out under lower ice cover circumstances, leading to higher aerial survey results in such years. In general, our study demonstrates the value of IPMs for monitoring wildlife populations under changing environments and for supporting science-based management decisions.
Keywords: integrated population model; IPM; state-space model; Bayesian; Pinniped; environmental change; haulout; long-term monitoring; wildlife management